Cone beam computed tomography evaluation of root canal morphology of maxillary premolars in North-West sub-population of Pakistan - Shahzad Ali Shah (Khyber Medical University Journal)
OBJECTIVES: To determine the number and configuration of canals in permanent maxillary premolars using Cone Beam Computed Tomography (CBCT) and the relationship between canals count and patient gender in northwest region of Pakistan.